Information security : 16th International Conference, ISC 2013, Dallas, Texas, November 13-15, 2013, Proceedings /: 16th International Conference, ISC 2013, Dallas, Texas, November 13-15, 2013, Proceedings. (2015) - Unknown
No abstract available